Is there a role for an embedded knowledge specialist in an organisation like an Academic Health Science Network? A retrospect of a one year pilot. (September 2021) - Giles, Carol; Day, Alison
Health Education England advocates for the introduction of more embedded knowledge specialist roles within healthcare organisations to save healthcare staff time ensuring that evidence from research, examples of good practice and learning from staff know-how and organisational knowledge are used to inform policy and practice. In 2020, a pilot was established to explore how a knowledge specialist role could bring benefits to the specialist business of an Academic Health Science Network in the South West of England. Using the structure of a retrospective learning after technique, this paper explores the rationale for the pilot, considers what was actually achieved despite the COVID-19 pandemic and examines reasons for successes and disappointments. Four key lessons are gathered that can be applied by anyone introducing a new knowledge management or embedded knowledge specialist service. The study concludes by outlining the unique contribution that an embedded knowledge specialist brings to the team to produce a tailored knowledge management service that saves staff time, keeps staff informed and connected while evolving to meet the ever changing priorities of complex healthcare organisations.